2019
DOI: 10.1097/md.0000000000015533
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of posterior cranial fossa morphology in the decompression of Chiari malformation type I

Abstract: Posterior fossa decompression (PFD) is the standard procedure for the treatment of Chiari malformation type I (CMI). Although most patients have satisfactory surgical outcomes, some show no improvement or even a worsening of symptoms. Patient selection is thought to account for these different surgical outcomes. Our aim was to evaluate the predictive value of the preoperative posterior cranial fossa (PCF) morphology on the efficacy of PFD. Data from 39 CMI patients with CMI-related symptoms who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Of these, 44 were rejected for not meeting the inclusion criteria or for being off-topic. Thirty-five were selected 7-40 for this systematic review (Appendix III, https://www.cns.org/guidelines/browse-guidelines-detail/2-symptoms).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 44 were rejected for not meeting the inclusion criteria or for being off-topic. Thirty-five were selected 7-40 for this systematic review (Appendix III, https://www.cns.org/guidelines/browse-guidelines-detail/2-symptoms).…”
Section: Resultsmentioning
confidence: 99%
“…In their study, while symptom recurrence did not differ as a function of the degree of tonsillar ectopia, patients with both ventral and dorsal decrease in CSF flow after surgery had reduced recurrence rates and patients with just dorsal decrease flow had larger recurrence rates. Liu et al found that posterior cranial fossa morphology did not predict response to posterior fossa decompression in CM1 [ 18 ]. Some studies have found that syrinx size change and tonsillar tip distance from foramen magnum do not have a predictive association with outcome or recurrence, while others have found an association between syrinx size reduction and postoperative symptomatic improvement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that syrinx size change and tonsillar tip distance from foramen magnum do not have a predictive association with outcome or recurrence, while others have found an association between syrinx size reduction and postoperative symptomatic improvement [19]. Studies looking at clinical features that predict CM1 recurrence have found that longer duration of headache, frontal headache, and vertigo independently increased the likelihood of symptom recurrence after decompression, and preoperative upper limb numbness and weakness are unfavorable factors predicting the outcome of posterior fossa decompressions in patients with CM1 [12,18]. Prognostic tools including the Chiari Severity Index and a points-based algorithm of Thakar et al have been developed to consolidate clinical and neuroimaging features that predict recurrence; however, Feghali et al's external validation study concluded that these scoring systems failed to provide prediction value of clinically meaningful improvement following decompression [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Alperin et al [ 23 ] suggested that physiological measures can be stronger predictors than morphological measures of posterior cranial fossa after FMD for CMI. Liu et al [ 24 ] concluded that the morphology of the posterior cranial fossa cannot predict the response to FMD in patients with CMI. Our study revealed no significant changes in the bone morphometric parameters of the craniocervical junction, as well as the atlanto-occipital instability, such as the Wiesel-Rothman interval, basion-axial interval, and ADI.…”
Section: Discussionmentioning
confidence: 99%